Behavioural and transcriptional plasticity in striatal circuits - Ferreira, Pedro Nuno Galvão (2015)
The central nervous system mediates the relationship between an organism and the external and internal worlds, building a physiologic bridge that is shaped by a plethora of stimuli and may involve cellular and molecular processes of different orders and diverse nature. This thesis explores plasticity both at the circuit and molecular levels.